An Ordinance Prohibiting the Sale of Arms, Ammunition, or Spiritous Liquors to the Indians, in Acts, Resolutions and Memorials Passed at the Several Annual Sessions of the Legislative Assembly of the Territory of Utah, at 63, § 1 (Henry McEwan 1866) - (:unkn) unknown (My University, 1850)
That if any person shall hereafter trade or give any guns, rifies,pistols or any other deadly weapons, ammunition or spirituous liquors to any Indian, without having a license, he shall, on conviction thereof before any Justice of the Peace, he fined in a sum not exceeding one hundred dollars for each offense, and also forfeit all the property received from the Indian, which shall be sold and the proceeds thereof paid into the public treasury."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES; TRANSFER